Capillary barrier effect on the response of residual slope to rainfall infiltration - Chai, Erwin Pak Shin (2008)
Rainfall-induced slope failure is a common problem in areas covered by residual soil in tropical countries. The soil exists in unsaturated condition as ground water table is located well below the ground surface. Rainfall infiltration results in a reduction of matric suction of soil which in turn reduces the soil shear strength, and subsequently triggers the slope failure. Natural formation of the residual soil has lead to the variation of hydraulic conductivity in which soil closer to the ground surface usually has lower permeability as compared to the deeper layer. This condition causes the development of capillary barrier effect at the interface. The water accumulates at the interface and flow for some distance down-slope before it manages to infiltrate into the deeper layer. The distance that the water has to travel before breakthrough is referred as the water diversion length. Numerical simulation using SEEP/W was performed in this study to determine the water diversion length for two cases representing natural slopes i.e. Silty SAND over SAND and Silty SAND over Highly Weathered Granite. Parametric study was performed to study the effect of several variables including hydraulic conductivity of soil, thickness of layers, slope dip angle and the rate of infiltration. Results show that the diversion length is linearly correlated with the difference in the permeability of two soil layers and slope dip angle. The effect of rainfall infiltration depends on the saturated permeability of the upper layer (MRL). The optimum thickness of MRL obtained in this study is 1.5m. Results of numerical analysis are compared with analytical method by Ross model, however good agreement between the two methods was not reached because the difference in saturated hydraulic conductivity of the soils used is not very big. Moreover, under an infiltration rate, the maximum suction existing in the CBL should be as low as possible while the maximum suction attained in the MRL should be as high as possible, which was not the case especially for Silty SAND over Highly Weathered Granite.